Success rate of electromagnetic navigation system on ventriculo-peritoneal shunt versus standard shunt placement in patients with hydrocephalus - Dawood, Aamir; Yasir, Muhammad (International Journal of Clinical Trials, 2019)
Background: Accuracy of ventriculoperitoneal shunt with the development of frameless neuronavigation in the field neurosurgery has been validated in different parts of the world. The objective of this study was to compare the success of electromagnetic (EM) navigation system on ventriculoperitoneal (VP) shunt versus standard shunt placement in patients with hydrocephalus. Methods: This randomized controlled trial was carried out in the Department of Neurosurgery, Multan. This study was approved by the Ethical Review Committee of Nishtar Hospital Multan. Study subjects were selected after an informed consent. Patients were grouped as (A) who received EM and (B) who received routine shunt surgery. Patients with shunts were followed up at the end of 3 months and post-operative CT was performed at the end of 3 months. Both groups were compared in terms of success by using chi-square test. Results: Among 100 study cases, mean GCS was 12.30±1.85 (with minimum GCS was 9 while maximum was 15) and mean duration of hydrocephalus was noted to be 6.80±2.02 weeks. Forty five (45%) were presented with mild hydrocephalus while 55 (55%) presented with moderate hydrocephalus. Grade outcome (post-operative) was noted in 78 (78%) of our study cases, grade 2 in 18 (18%) while grade 3 (failure) was noted in only 4 (4%). Conclusions: The usage of electromagnetic (EM) navigation on ventriculoperitoneal (VP) shunt is safe and reliable which is beneficial for optimal positioning and trajectory of ventricular catheters in adult patients with hydrocephalus.